1987
DOI: 10.1002/cne.902610309
|View full text |Cite
|
Sign up to set email alerts
|

Corneal sensory pathway in the rat: A horseradish peroxidase tracing study

Abstract: The methods of transganglionic transport of horseradish peroxidase (HRP) and horseradish peroxidase--wheat germ agglutinin (HRP-WGA) were used to determine the location within the trigeminal ganglion of the primary afferent neurons that innervate the rat central cornea, and the brainstem and spinal cord termination sites of these cells. In each of 18 animals, solutions of HRP or HRP-WGA were applied to the scarified corneal surface and allowed to infiltrate into the corneal epithelium and stroma for 15 minutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
99
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(115 citation statements)
references
References 29 publications
16
99
0
Order By: Relevance
“…and Burton, 1981;Marfurt and del Toro, 1987;Anton and Peppel, 1991;Takemura et al, 1991;Lu et al, 1993;Strassman and Vos, 1993;Strassman et al, 1994;Meng and Bereiter, 1996;Gong et al, 2003). Noxious sensory input from other trigeminal structures such as the temporomandibular joint (Hathaway et al, 1995) and masseter muscle (Ikeda et al, 2003), however, also activates neurons at the ventral Vi/Vc transition, suggesting a broader role in trigeminal nociception.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and Burton, 1981;Marfurt and del Toro, 1987;Anton and Peppel, 1991;Takemura et al, 1991;Lu et al, 1993;Strassman and Vos, 1993;Strassman et al, 1994;Meng and Bereiter, 1996;Gong et al, 2003). Noxious sensory input from other trigeminal structures such as the temporomandibular joint (Hathaway et al, 1995) and masseter muscle (Ikeda et al, 2003), however, also activates neurons at the ventral Vi/Vc transition, suggesting a broader role in trigeminal nociception.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the proposal that different subnuclei of the Vsp serve different aspects of trigeminal function (Renehan and Jacquin, 1993;Bereiter et al, 2000;Sessle, 2000). In rodents the ocular surface is represented mainly at two spatially distinct regions: the trigeminal subnucleus interpolaris-caudalis (Vi/Vc) transition and subnucleus caudalis-upper cervical spinal cord (Vc/C1) junction regions (Marfurt and del Toro, 1987;Lu et al, 1993;Strassman and Vos, 1993;Meng and Bereiter, 1996;Gong et al, 2003). The present study measured tear volume and recorded single unit activity to test the hypothesis that the rostral Vi/Vc transition and caudal Vc/C1 junction regions contribute differentially to the control of fluid homeostasis of the ocular surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nociceptin immunoreactivity in the superficial dorsal horn is not affected by dorsal root rhizotomy, suggesting that at the spinal cord level nociceptin is produced by central rather by primary afferent neurons [162]. In tracing experiments, it has been demonstrated that the primary trigeminal fibers descend to the superficial layer of the dorsal horn of the cervical spinal cord [130]. About 70% of neuronal cells in trigeminal ganglia are nociceptin immunopositive [103].…”
Section: Sensory Nervous Systemmentioning
confidence: 99%
“…The sensory neurons innervating the cornea are located in the medial or ophthalmic region of the trigeminal nerve. 24 In cornea, fibers forming the basal epithelial plexus and branch into the epithelium originate from myelinated Ad-and unmyelinated C-fibers. 25 Ad fibers participate in mechanical sensitivity in cornea, which is very important for the blinking reflux leading to tear secretion.…”
Section: Discussionmentioning
confidence: 99%